DINAMIKA PENERAPAN HUKUM HUMANITER DALAM KONFLIK ISRAEL– PALESTINA: ANTARA NORMA DAN REALITAS - Andry Kuswoyo; Fajar Catur Prasetyo, Tarsisius Susilo, Rapy Tadung, Andar Dodianto Panggabean (INTELIGENSIA MEDIA, 2025)
The protracted conflict between Israel and Palestine has posed persistent challenges to the application and enforcement of international humanitarian law (IHL). Despite numerous international conventions aimed at protecting civilians during armed conflict, both state and non-state actors in this region have repeatedly acted in ways that test the limits and flexibility of IHL principles. This article explores the legal and ethical dynamics of IHL in the Israel-Palestine conflict, analyzing core principles such as distinction, proportionality, and military necessity through case studies of military operations in Gaza and the West Bank. It also highlights the roles of international organizations such as the United Nations and the International Criminal Court in promoting accountability. By examining legal interpretations, political contexts, and evolving military technologies, this study identifies gaps and contradictions that hinder effective enforcement. The analysis suggests that a multidimensional approach—combining legal advocacy, diplomatic engagement, and ethical military conduct—is essential to reinforce humanitarian norms and reduce civilian harm in future conflicts